2017
DOI: 10.4103/jovr.jovr_92_16
|View full text |Cite
|
Sign up to set email alerts
|

Validation of farsi translation of the ocular surface disease index

Abstract: Purpose:To develop and validate a Farsi version of Ocular Surface Disease Index (OSDI) for the Iranian population.Methods:This study was a translation and cross-cultural adaptation and validation of Farsi version of OSDI. Four bilingual (English-Persian) individual including three physicians and one native English teacher were asked to translate the original English OSDI questionnaire in Farsi. Following back and forth translation, integration and pilot check, the translation team came to consensus on translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 7 publications
2
24
0
2
Order By: Relevance
“…The OSDI total score can be used to classify the respondent's dry eye symptoms as normal (0-12 points), mild (13-22 points), moderate (23-32 points), or severe (33-100 points) [30][31][32]. This questionnaire was originally developed in English [29] with subsequent translations and validations in Portuguese [33], Spanish [34], Farsi [35], Bahasa [36], Chinese [37], Filipino [38], and Japanese [39]. However, caution should be applied when using it, given that the cutoff values for DED differ across languages, with a threshold of 27.2 and 36.3 points in the Chinese and Japanese versions, respectively [37,39,40].…”
Section: Ocular Surface Disease Index (Osdi)mentioning
confidence: 99%
See 1 more Smart Citation
“…The OSDI total score can be used to classify the respondent's dry eye symptoms as normal (0-12 points), mild (13-22 points), moderate (23-32 points), or severe (33-100 points) [30][31][32]. This questionnaire was originally developed in English [29] with subsequent translations and validations in Portuguese [33], Spanish [34], Farsi [35], Bahasa [36], Chinese [37], Filipino [38], and Japanese [39]. However, caution should be applied when using it, given that the cutoff values for DED differ across languages, with a threshold of 27.2 and 36.3 points in the Chinese and Japanese versions, respectively [37,39,40].…”
Section: Ocular Surface Disease Index (Osdi)mentioning
confidence: 99%
“…The CLDEQ-8 can evaluate changes in subjective symptoms when changing contact lens type. [57] CDERQOL [54] NEI VFQ−25 [60] OCI [78] Insufficient * 4 DEQ [73] OSD [74] TERTC-DEQ [76] McMonnies questionnaire [80] Schein questionnaire [83] Women's Health Study questionnaire [87] SPEED [90] SANDE [92] DEQ-5 [43] No English, Portuguese, [33], Spanish [34], Farsi [35], Bahasa [36], Chinese [37], Filipino [38], Japanese (J-OSDI) [ : Good validity and reliability according to the PRO guidance; : Insufficient description of psychometric properties or poor validity and reliability; ×: No description of psychometric properties; N/A: Not applicable, score calculation method is not mentioned; Not scored *: There is no score for each question item. J-OSDI: Japanese version of the Ocular Surface Disease Index, OCI-C: Chinese version of the Ocular Comfort Index, J-CLDEQ-8: Japanese Contact Lens Dry Eye Questionnaire-8.…”
Section: Contact Lens Dry Eye Questionnaire-8 (Cldeq-8)mentioning
confidence: 99%
“…Both the Ocular Surface Disease Index (OSDI) and the Dry Eye-Related Quality-of-Life Score (DEQS)12 are widely used to assess subjective symptoms of DED in Japan, but the reliability and validity of the OSDI have not been confirmed in Japan 13. Determining the reliability and validity of the Japanese version of the OSDI (J-OSDI) is essential for making epidemiological and symptomatic comparisons with other countries 13–16…”
Section: Introductionmentioning
confidence: 99%
“…Subjective tests can always have some type of error (40), due to the fact that there are variables inherent to patients (41), which cannot be controlled either (42), and it should also be considered that objective tests are capable of generating a tear reflex (43). This alters the results of the tests (44), which could mean that the fewer invasive techniques are performed, the more reliable the result will be.…”
Section: Discussionmentioning
confidence: 99%
“…In countries such as France, Germany, Italy, Spain, Sweden, and the United Kingdom, it has been reported that dry eye syndrome produces an average net cost in treatment for the patient between $ 273,000 and $ 1,100,000 every year. In that sense, and considering that dry eye occurs in patients over 40 to prevent the disease and improve the health conditions of the Mexican population.…”
Section: Discussionmentioning
confidence: 99%